Strategic Methods to Reduce Globalization Company Risk: Alliances - Valentina Golea (Theoretical and Applied Economics, 2007)
Market globalization and impressive market growth force a lot of companies to declare themselves in the position of not having the critical strategic dimension, necessary for a successful competition gigantic markets. As a consequence, companies may be forced to resort more and more, to newer cooperation types, which were inconceivable in traditional economic development and when national markets prevailed. Signing alliances among companies may change the force field on national and international markets and may profoundly reconfigure the respective markets.